1973
DOI: 10.1530/jrf.0.0340347
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Contractions in the Ewe During Progestagen-Regulated Oestrus

Abstract: Summary. Parous ewes were treated orally or intravaginally with synthetic progestagen, or subcutaneously with progesterone. Treatment was begun on Day 8 or 10 of an oestrous cycle and continued for 13 to 17 days. At the oestrus following progestagen withdrawal, the uterus was exposed and uterine contractions observed. Each treatment reduced the number of uterine contractions moving towards the oviducts and increased the number moving towards the cervix. The altered motility pattern probably helps to account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This observation and further data obtained at estrus which showed that ewes in the SSE-APN group exhibited more (P<.05) total uterine contractions and more (P<.025) contractions migrating toward the oviduct than ewes in the NSE-APN group lend support to the Segerson et aL hypothesis. The finding that more uterine contractions migrated toward the oviduct at estrus than toward the cervix or in neither direction is in agreement with migration patterns previously reported (Brinsfield and Hawk, 1969;Hawk and Echternkamp, 1973). Previous studies with dairy cattle (Trinder et M., 1969;Julien et al, 1976) have demonstrated the efficacy of Se and Se plus vitamin E in decreasing the incidence of retained placenta, suggesting a possible effect of one or both of these nutrients on uterine muscular function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation and further data obtained at estrus which showed that ewes in the SSE-APN group exhibited more (P<.05) total uterine contractions and more (P<.025) contractions migrating toward the oviduct than ewes in the NSE-APN group lend support to the Segerson et aL hypothesis. The finding that more uterine contractions migrated toward the oviduct at estrus than toward the cervix or in neither direction is in agreement with migration patterns previously reported (Brinsfield and Hawk, 1969;Hawk and Echternkamp, 1973). Previous studies with dairy cattle (Trinder et M., 1969;Julien et al, 1976) have demonstrated the efficacy of Se and Se plus vitamin E in decreasing the incidence of retained placenta, suggesting a possible effect of one or both of these nutrients on uterine muscular function.…”
Section: Discussionsupporting
confidence: 90%
“…Ewes were checked for estrus twice daily and utilized for a 30-day period. At the onset of estrus, ewes were laparotomized and the uterus exteriorized for the quantitation of directional uterine contractions as described by Hawk and Echternkamp (1973). Uterine contractions were recorded for a lO-min period, and classified either as moving toward the oviduct or cervix or as moving in no apparent direction.…”
Section: Uterine Contraction Study Twenty-ninementioning
confidence: 99%
“…A comparison of uterine contractions during estrus in untreated ewes and during the ensuing estrus in progesterone-treated ewes indicated that each of the four progestogen treatments used in the present study reduced the number of contractions moving toward the oviducts and increased the number moving toward the cervix (Hawk and Echternkamp, 1973). Near and soon after the end of estrus the direction of uterine contractions in untreated ewe changes, apparently due to declining estrogen secretion, from predominantly toward the oviducts to predominantly toward the cervix (Hawk, 1975).…”
Section: Discussionmentioning
confidence: 52%
“…Uterine motility is a major contributing factor to sperm transport (Brinsfield and Hawk, 1969;Warren and Hawk, 1971;Hawk and Echternkamp, 1973;Hawk, 1983). Uterine contractions in ewes that have not lambed within the previous 90 d originate near the cervix and move toward the oviducts, whereas most contractions in d-30 postpartum ewes originate near the oviducts and move toward the cervix (Warren and Kiesling, 1982, 1983.…”
Section: Resultsmentioning
confidence: 99%